GAYA HIDUP PENGGEMAR K-POP (BUDAYA KOREA) DALAM MENGEKSPRESIKAN KEHIDUPANNYA STUDI KASUS K-POP LOVERS DI SURAKARTA - Puspitasari, Wulan (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
ABSTRACT-This research aims to: (1) identify the characteristics of K-Popfans inSurakarta; (2) identify the factors that encourage fans idolized K-Pop: and (3)describe how fans in expressing their penchant for K-Pop. This research usesqualitative methods. This method was chosen because of the qualitative research candescribe objects is based on the holistic based on the social reality which is occurredreal life. Type of this research is a case study of stake, because this research was tostudy, explain or interpret a case (case) in context naturally, without any interventionfrom outside parties.Source data obtained from studies library, event or activity, placeor location, the informant K-Poplovers who joined in community UKLI (United KPopLoversIndonesia) District Solo and documents (archives). Data collectiontechniques used are interviews, direct observation, and analysis of documents. Thevalidity of the data obtained through triangulation triangulation of data or resources.Data analysis techniques used in this research, a model analysis of the interactive(interactive model of analysis) which includes 4 components namely (1) datacollection, (2) reduction of data, (3) presentation of data, (4) the withdrawal of theconclusion.Based on the results of research it can be concluded that K-Poplovers at UKLI(United K-PopLovers Indonesia) District of Solo are mostly teenager who still studyboth in junior high school and College and they have their own Koreanname. Theychoose K-Popas their idol, for the fans in terms of vocal and dancing abilities as wellas in terms of their physical. Behavior or activity typical of fans in expressing to theK-Popcraze manifested through the high intensity of the hear music and watch musicvideos boy band and their idol girlband, collectibles (CD of original music, songs,videos, merchandise from boyband and a girlband K-Popof jackets, t-shirts, hats,posters, etc.), with enthusiasts through the expression community join in SoloDistrict, following UKLI K-fest, K-Pop concert.Key Words: K-Pop, life style, cultural studies.